Só é velho quem pensa quem é: cuidado de si e estética da existência nos Grupos de Convivência de Toledo-Pr - Spies, Márcia Franciele (2019)
“Grow older is the most modern thing”. In the verses by Arnaldo Antunes we find the perfect synthesis to describe one of mankind's greatest achievements in the 21ST century: the increase in the number of longevits. This change in the age profile of contemporary society is configured to live more and better. To jovialize old age and take away at all costs ageing risk. In this sense, It is also perceived alterations in how the elderly understands its ageing by recognizing in it a coping phase. A moment in which you can develop new ways to "take care yourself" in a reinvention process the living old age act, not excluding death and disease from the life course, but invented positive ways recreating themselves and, they are assuming for themselves the responsibility that this life phase brings with all its losses and gains. In the Toledo Coexistence Groups, the elders assume the protagonist role in their history, in order to bring more joy and lightness to life, to free themselves from the shackles to live old age as a privilege. In this premise, this study has the old age to research central theme as a full event, celebrating life moment and the possibility to invent different ways of existence, a phase in which the subject takes the his story responsibility to himself and contravene the ready models, getting rid of the impositions. To this end, we used Michel Foucault's studies on existence and self-care aesthetics. These studies depart from the ethical choice linked to an existence aesthetic, emphasizing aspects related to health care, affectivity, sexuality, political and social participation. In this line, we highlight the research on the old age by Silvana Tótora, she which has as an analytical perspective the consecrating of old age as power, a resistance privileged moment to power mechanisms and hegemonic models that are focused to stall aging in the eternal youth pursuit.